[Man or a mouse ; King Copra ; Voter's profile [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
LDP presidential bet Ramon Mitra on his involvement in the coconut levy and the legality of the ranches cast doubt. Danding Cojuangco refutes involvement in the coconut levy. The candidates political machinery as the ultimate decider of the elections.